Physical Fitness and Anthropometric Measures of Young Brazilian Judo and Wrestling Athletes and Its Relations to Cardiorespiratory Fitness - Vitor Marques; Victor Coswig; Ricardo Viana; Acácia Leal; Fagner Alves; Ana Alves; Gabriela Teles; Carlos Vieira; Maria Silva; Douglas Santos; Paulo Gentil (MDPI AG, 2019)
This study aimed to compare the anthropometric profile and physical fitness of young judo and wrestling athletes. Twenty-four young athletes (judo (n = 13) and wrestling (n = 11)) participated in this study. The first visit involved anthropometric and flexibility evaluation, abdominal endurance test, upper limbs resistance and cardiorespiratory test. After 48 h, horizontal jump test (HJT), vertical jump test (VJT), medicine ball throw test (MBT), chin-up test (CUT), chin-up isometric test (CUIT) and the anaerobic resistance test were performed. Judo athletes presented greater values for body mass (p = 0.020), height (p = 0.010), and body mass index (p = 0.026) than wrestlers. Judo athletes also performed better for abdominal endurance (p = 0.044), upper limb resistance tests (p < 0.001), VJT (p = 0.022) and MBT (p = 0.023) than wrestling athletes. These results suggest that young judo athletes presented a higher performance in abdominal endurance, upper limbs resistance, HJT, VJT and MBT than wrestling athletes, suggesting that strength and conditioning are related to modality specificity.